Liberalization, Endogenous Institutions, and Growth : A Comparative Analysis of Agricultural Reforms in Africa, Asia, and Europe - Swinnen, Johan F.M. (World Bank, 2013)
Thirty years ago, a vast share of low- and middle-income countries was heavily state controlled. The liberalizations of the 1980s and 1990s had greatly different effects on growth in countries in Africa, Asia, and Europe. A comparative framework is used to document these differences, and a model is developed to formally analyze how liberalization affects production and income distribution when the institutions that govern production and exchange are also affected. Hypotheses are derived for how endogenous institutional adjustments affect the growth response to liberalization. These insights motivate a series of explanations for the differences in performance across regions and commodities following liberalization.